2017
DOI: 10.1016/j.carbpol.2017.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of maltoheptaose-b-PMMA block copolymer systems: 10 nm Resolution in thin film and bulk states

Abstract: This paper describes the self-assembly of oligosaccharide-based hybrid block copolymers (BCPs) consisting of maltoheptaose (MH) and poly(methyl methacrylate) (PMMA) into 10nm scale lamellar and cylindrical phases depending on the volume fractions of MH (ϕ) and the annealing process. Time resolved SAXS study of the BCP bulk samples during thermal annealing indicated that the BCPs phase separate into 10nm scale periodical structures. The solvent vapor annealing induced self-organizations of the BCP into differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The saccharide-containing conjugates examined all show one detectable T g , which can be attributed to the higher- T g saccharides being the minority components. Similar observations of a single T g transition have been reported in other compositionally asymmetric oligosaccharide-containing diblock copolymers. ,, For the MT-containing conjugates, the measured T g reflects mostly that of the PS component. Their values are higher than N 3 –PS–N 3 because the PS chains are tethered on both ends to the rigid high- T g MT.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The saccharide-containing conjugates examined all show one detectable T g , which can be attributed to the higher- T g saccharides being the minority components. Similar observations of a single T g transition have been reported in other compositionally asymmetric oligosaccharide-containing diblock copolymers. ,, For the MT-containing conjugates, the measured T g reflects mostly that of the PS component. Their values are higher than N 3 –PS–N 3 because the PS chains are tethered on both ends to the rigid high- T g MT.…”
Section: Resultssupporting
confidence: 84%
“…Similar observa-tions of a single T g transition have been reported in other compositionally asymmetric oligosaccharide-containing diblock copolymers. 20,34,35 For the MT-containing conjugates, the measured T g reflects mostly that of the PS component. Their values are higher than N 3 −PS−N 3 because the PS chains are tethered on both ends to the rigid high-T g MT.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum solubility of lignin (99.88%) was obtained with a 7:3 volume ratio of GVL to water. This could be explained by Hildebrand solubility theory [ 44 ]; the maximum solubility of lignin should be obtained when the solubility parameter of the solvent mixture is close to the solubility parameters of lignin. The effects of the volume ratio of GVL to water on the particle sizes of LNPs were investigated and the results are shown in Figure 1 b.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Cushen et al linked MH to poly­( para -trimethylsilylstyrene) (PTMSS) in MH- b -PTMSS with an N of 22, and this copolymer also phase separated into cylinders of L 0 = 8.3 nm. Noronha et al demonstrated that MH- b -PMMA with an N of 34 could phase separate into a cylindrical morphology with an L 0 = 8.3 nm. Additionally, Sakai-Otsuka and colleagues linked poly­(3-hexylthiophene) with peracetylated maltoheptose in P3HT- b -AcMal 7 with an M n of 5670 g mol –1 and demonstrated phase separation into a lamellar morphology with an L 0 = 12.2 nm.…”
Section: Introductionmentioning
confidence: 99%